2012
DOI: 10.1007/s12282-012-0350-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ALDH1 in axillary lymph node metastases is a prognostic factor of poor clinical outcome in breast cancer patients with 1–3 lymph node metastases

Abstract: Evaluation of biomarker expression in ALNM could be useful for prognosis in breast cancer patients with 1-3 metastatic lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
5
24
1
Order By: Relevance
“…Only few previous studies have thus far compara- tively studied CSCs in primary tumors with their associated metastases. It was reported that increased ALDH1 expression in patients with breast cancer lymph node metastases serves as a prognostic factor of poor clinical outcome (26).…”
Section: Discussionmentioning
confidence: 99%
“…Only few previous studies have thus far compara- tively studied CSCs in primary tumors with their associated metastases. It was reported that increased ALDH1 expression in patients with breast cancer lymph node metastases serves as a prognostic factor of poor clinical outcome (26).…”
Section: Discussionmentioning
confidence: 99%
“…For references that did not provide HRs, we referred to the methods described by Tierney et al . [20] to obtain the HRs using the data and figures from the original papers [19,21-23]. …”
Section: Methodsmentioning
confidence: 99%
“…The hazard ratio for patients with one to three node involvement compared with none was 1.2 (95% CI=0.8-1.9) and it was 2.5 (95% CI=1.8-3.4) among four or more involved nodes, respectively. Other studies reported the significant higher HR of DFS among patients with than those without axillary lymph node metastasis (ALNM) (Rosa Mendoza et al, 2013;Nogami et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic and predictive factors for breast cancer include classical clincopathological features derived from breast cancer samples including stage, tumor size, histological subtype and grade, lymph node metastases (Rosa Mendoza ES et al, 2013;Nogami T et al, 2014 ), type of tumor, lymphatic and vascular invasion (Jatoi et al, 1999 ), and hormone receptor status (Weigel, 2010).…”
mentioning
confidence: 99%